The Analysis of Financial Performance to Capital Structure - Berlian Karlina (International Journal of Business Studies, 2021)
Capital structure is very important in guaranteeing company sustainability, establishing capital structures need to consider some variables can affect because it will directly affect the company's condition in determining ability of the company to endure and develop. The study was aimed to examine effect of profitability, liquidity, company size and asset structure on capital structure at company of large trade sub sectors of production and consumer goods in the Indonesia Stock Exchange (IDX) period 2014-2018. The sampling technique used puposive sampling, the number of samples used was 9 companies from a population of 28 companies. Analytical tool used in this study is multiple linear regression assisted by SPSS version 20.0 programs with enter methods. Results of this study indicate that the profitability, liquidity and asset structure are negatively and significantly affected by the capital structure while the company size has a positive and significant effect on capital structure.